Improving Collaborative Ability and Learning Achievement in Mathematics Through the Project-Based Learning (PjBL) Model Using Diagram Image Media for Class VI Students of SD Negeri Purwoharjo Academic Year 2021/2022 - Ritartini (Universitas Islam Indonesia, 2023)
This research aims to improve students' collaboration skills and learning achievement in class VI mathematics, SD Negeri Purwoharjo for the 2021/2022 academic year through the application of the project-based learning (PjBL) learning model. This type of research is Classroom Action Research which was conducted over two cycles with each cycle consisting of 2 meetings. The subjects in this study were fifth-grade students at SD Negeri Purwoharjo, which consisted of 5 students. Data collection techniques in this study through observation. The study results showed an increase in students' collaboration skills, where in cycle I, an average score was obtained of 3.18 with a percentage of 79.44% and in cycle II an average value was obtained of 3.47 with a percentage of 86.81%. While the results of student learning achievement data also showed an increase, this is evident in the first cycle of students who fulfilled the Minimum Completeness Criteria obtained an average value of 60%, and in the second cycle students who fulfilled the Minimum Completeness Criteria obtained an average value of 100%. Therefore, the application of the project-based learning (PjBL) learning model can increase the collaboration abilities and learning achievements of students in mathematics class VI at SD Negeri Purwoharjo for the 2021/2022 academic year.